Does Instrumental Reciprocity Crowd out Prosocial Behavior? - Åshild A. Johnsen; Ola Kvaløy (Center for Economic Studies and ifo Institute (CESifo), 2014)
In repeated games, it is hard to distinguish true prosocial behavior from strategic instrumental behavior. In particular, a player does not know whether a reciprocal action is intrinsically or instrumentally motivated. In this paper, we experimentally investigate the relationship between intrinsic and instrumental reciprocity by running a two-period repeated trust game. In the strategic treatment' the subjects know that they will meet twice, while in the non-strategic treatment' they do not know and hence the second period comes as a surprise. We find that subjects anticipate instrumental reciprocity, and that intrinsic reciprocity is rewarded. In fact, the total level of cooperation, in which trust is reciprocated, is higher in the non-strategic treatment. This indicates that instrumental reciprocity crowds out intrinsic reciprocity: If one takes the repeated game incentives out of the repeated game, one sees more cooperation.
Keywords: C91; 330; reputation; reciprocity; crowding out; experiment